The Effects and Safety of Silymarin on β-thalassemia in Children and Adolescents: A Systematic Review based on Clinical Trial Studies - Rahimi-Dehkordi, Nasim; Heidari-Soureshjani, Saeid; Sherwin, Catherine MT (Reviews on Recent Clinical Trials, 2024)
Backgroundβ-thalassemia imposes significant complications on affected patients. Silymarin, a natural flavonoid complex, has potential therapeutic properties.ObjectiveThis systematic review aims to comprehensively evaluate the literature on the mechanistic effects of Silymarin on β-thalassemia outcomes in children and adolescents.MethodsA systematic search of electronic databases, including MEDLINE/PubMed, Embase, Scopus, Cochrane Library, and Web of Science (WOS), was done to identify relevant clinical trials before January 2024. Various data were extracted, including study characteristics, outcomes measured (hematological parameters, oxidative stress markers, iron metabolism, and other outcomes), proposed mechanisms, and safety.ResultsBy iron chelation effects, Silymarin can reduce reactive oxygen species (ROS) production, increase intracellular antioxidant enzyme glutathione (GSH), and insert antioxidant effects. It also attenuated inflammation through reduced tumor necrosis factor-alpha (TNF-α), transforming growth factor-β1 (TGF-β1), interferon-gamma (IFNγ), C-reactive protein (CRP), interleukin 6 (IL-6), IL-17, and IL-23 levels and increase in IL-4 and IL-10 levels. By reducing iron overload conditions, Silymarin indicates modulatory effects on immune abnormalities, inhibits red blood cell (RBC) hemolysis, increases RBC count, and minimizes the need for a transfusion. Moreover, it reduces myocardial and hepatic siderosis, improves liver function tests, and modifies abnormal enzymes, particularly for aspartate transaminase (AST), alanine transaminase (ALT), alkaline phosphatase (ALP), total bilirubin, and total protein levels. Silymarin also reduces iron overload, increases antioxidant and anti-inflammatory capacity in cardiomyocytes, and reveals antioxidant effects.ConclusionSilymarin indicates promising effects on various aspects of children and adolescents with β-thalassemia and has no serious side effects on the investigated dosage.
Keywords: Silymarin